Tren Desain Kurikulum Adaptif di Era Disrupsi Sebagai Strategi Manajerial Menuju Pendidikan Masa Depan - Ma’shum Thoyib (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to analyze how adaptive curriculum encourages learning flexibility and its contribution to improving the quality of education in the era of disruption. The research approach used is qualitative with a case study type. This research was conducted at MI Al Khoiriyyah, Muara Bungo, Indonesia. Data collection techniques include in-depth interviews, observation, and documentation. Data analysis was carried out through data reduction techniques, data presentation, and drawing conclusions, while the validity of the data was checked by triangulation of sources and techniques. The results of the study indicate that adaptive curriculum provides flexible space for teachers to adjust learning methods and materials according to student characteristics, supported by the visionary managerial leadership of the principal and the use of digital technology. These findings show that the success of adaptive curriculum is greatly influenced by the synergy between educational actors and supporting facilities that are responsive to change. The contribution of this study lies in a comprehensive understanding of the practice of implementing adaptive curriculum and strategic recommendations for the development of future education policies.